The “angioletti” of Palermo: the health and development of mummified non-adults in late modern Palermo, Sicily (1787–1880 CE) - Squires, Kirsty; Viner, Mark; Hoban, Wayne; Loynes, Robert; Van Schaik, Katherine; Piombino-Mascali, Dario (Frontiers in Medicine, 2024)
The Capuchin Catacombs in Palermo, Sicily, have been home to non-adult mummified remains since the seventeenth century CE. Despite the increasing numbers of scientific studies conducted at this site, very little research has focused specifically on the youngest members of late modern (1787–1880 CE) society. This research aims to redress the balance by examining 43 individuals to gain insight into the demographic profile of mummified non-adults, to characterize their health status and possible cause of death, and to better understand the funerary treatment offered to the youngest members of society. A portable X-ray unit was used to capture anteroposterior and lateral images of each mummy; this facilitated age estimation, the identification of pathological and/traumatic lesions, and evidence of conservation and the mummification process more generally. This study revealed that regardless of age and health status at the time of death, the mortuary rite performed was primarily influenced by the wealth and social standing of the deceased’s kin. No demographic trends were observed in the data and the lack of evidence of metabolic, neoplastic, and traumatic bone lesions suggest these non-adults died from short-term, acute illnesses. Even when individuals did display evidence of chronic health conditions that would have impacted their day-to-day lives (e.g., B035), they were not excluded from this mortuary tradition on the basis of their long-term health and care requirements in life. Artifacts were found with all individuals examined and were associated with the mummification process, conservation of mummies, and/or their display. This research has ultimately demonstrated that non-invasive imaging can be used to gain a more comprehensive understanding of the lives and deaths of non-adults inhabiting late modern Palermo.